2020
DOI: 10.1016/j.immuni.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8-Dependent Inflammatory Responses Are Controlled by Its Adaptor, FADD, and Necroptosis

Abstract: Highlights d Non-cleavable caspase-8 (caspase-8 DA) causes inflammation, blocked by necroptosis d Inflammation in Casp8 DA/DA Mlkl À/À mice is prevented by ablation of one allele of Fadd d Full deletion of Fadd in Casp8 DA/DA Mlkl À/À mice causes Casp1-dependent lethality d Non-cleavable caspase-8 induces ASC oligomerization in absence of FADD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 57 publications
4
83
1
Order By: Relevance
“…Furthermore, it might be suggested that reprogramming of pyroptosis through targeting the proteins of the extrinsic cell death pathway to induce different forms of programmed cell death may lead to a less pathogenic phenotype of SARS-CoV-2. This strategy can be achieved due to the tight cross talk between pyroptosis and apoptosis mediated by the members of extrinsic cell death pathways 25,26,69 . In particular, in recent studies it was shown that inflammasome adaptor ASC recruits procaspase-8 through a PYD/DED interaction 32 .…”
Section: Targeting Dd-mediated Network At the Later Stages Of Sars-cmentioning
confidence: 99%
“…Furthermore, it might be suggested that reprogramming of pyroptosis through targeting the proteins of the extrinsic cell death pathway to induce different forms of programmed cell death may lead to a less pathogenic phenotype of SARS-CoV-2. This strategy can be achieved due to the tight cross talk between pyroptosis and apoptosis mediated by the members of extrinsic cell death pathways 25,26,69 . In particular, in recent studies it was shown that inflammasome adaptor ASC recruits procaspase-8 through a PYD/DED interaction 32 .…”
Section: Targeting Dd-mediated Network At the Later Stages Of Sars-cmentioning
confidence: 99%
“…Bound TNFR1 interacts with TNFR1-dssociated death domain protein (TRADD), through its DD, which enables the formation of "Complex I". The subsequent formations of "Complex II" ("IIa" or "IIb") operate as molecular platforms to regulate the activation and functions of CASP8 (or CASP10, in some cases) [76,77]. CASP8 activation leads to RCD following two different pathways.…”
Section: Extrinsic Apoptosismentioning
confidence: 99%
“…CASP8 activation is the key process of extrinsic apoptosis; its regulation is complex and also involved in inflammation and antiviral response [77]. cFlip is one of the key components that promotes or inhibits CASP8 oligomerization and ensuing activation by autoproteolytic cleavage.…”
Section: Extrinsic Apoptosismentioning
confidence: 99%
“…The current protocol focuses on the generation of a Casp8 FL122/123GG missense mutation, but it can be adapted to introduce any missense or nonsense mutation. For complete details on the use and execution of this protocol, please refer to Tummers et al. (2020) .…”
mentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Tummers et al. (2020) .…”
mentioning
confidence: 99%